A Multi-level Semantics Formalism for Multi-Agent Microservices - Panisson, Alison R.; Farias, Giovani P. (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2024: Anais da XXXIV Brazilian Conference on Intelligent Systems, 2024)
Operational semantics is a fundamental approach to the formalisation of programming languages and almost a standard when it comes to agent-oriented programming languages. It helps ensure the correctness of interpreters, facilitates their implementation, and supports proofs of important properties. However, in the literature, there are few attempts of formalising multi-level operational semantics for multi-agent systems which allows the formalisation of all levels of abstraction in those systems. Also, recently, authors have started to discuss a new approach to build multi-agent systems known as multi-agent microservices, arguing that microservices represent a potential point of convergence between modern software engineering and multi-agent systems. We agree that microservices could be a useful approach to think of multi-agent systems and, in this paper, we propose a multi-level semantics to formalise this new approach to build multi-agent systems based on the abstraction of microservices. We not only introduce a template for those formalisation but we also show how our operational semantics style promotes desired characteristics of modularity, reusability, and a clear specification of shared communication artifacts in multi-agent microservices.